KH. Abdul Wahid Hasyim’s Paradigm on Freedom of Learning in Madrasa - Azis, Azis (Nur Science Institute, 2023)
In the early twentieth century, Indonesia witnessed the flourishing of madrasa as a new model for Muslim educational institutions to respond to public schools established by the Dutch colonial era. Abdul Wahid Hasyim was one of the prominent Muslim intellectuals who introduced some approaches in madrasa learning process in which different from the traditional learning system in the pesantren. The purpose of this paper is to elaborate on Abdul Wahid Hasyim’s thoughts on freedom of learning in madrasa using a historical approach to understand the historical context of Hasyim’s ideas. As a result, this paper argues that Wahid Hasyim offered a mixed curriculum in madrasa by combining Islamic and secular subjects that are considered useful for students in the future. Another finding is that Wahid Hasyim preferred the tutorial method in the learning process, which replaced teacher-centered learning, as is common in pesantrens. To some extent, this method of learning is similar to student-centered learning in contemporary pedagogy.